Development of technological pedagogical content knowledge through project–based learning - Hosseini, Z.; Tee, M.Y. (2011)
The aim of this case study was to better understand how TPCK can be developed through Project-based Learning (PjBL). Accordingly, a course was designed and a purposively sampled group was selected for collecting in-depth data. The findings of the study demonstrated that teachers' knowledge and conception of using technology for teaching developed in three levels. With each level, there was an improvement of teachers' TPCK and its components as a result of performing PjBL activities. First level was limited to using technology for exhibiting curriculum information. The participants used software and Internet facilities for exhibiting curriculum information corresponding to the content. In the second level, the participants focused on using technology to present content and materials. The results indicated that in this level although two components of the participants' TPCK, viz. TCK and PCK developed, considering technology as a learning tool (TPK) appeared to be missing. However, in the third level they developed the ability to use technology for enhancing teaching and learning.